A SCOPING REVIEW OF TEACHING AND LEARNING OF ENGLISH AS AN ADDITIONAL LANGUAGE AMONG AUTISTIC INDIVIDUALS (Malaysian Journal of Learning and Instruction, 2022)
Purpose - The purpose of this scoping review was to examine research studies relating to autistic students in learning English as anAdditional Language (EAL) to outline potential research agendas and to inform EAL educators of current related issues.Methodology - PRISMA-ScR protocol outlined by Tricco et al. (2018) was followed when selecting the relevant studies publishedbefore July 2020 from six prominent databases: Education database, ERIC; Linguistics database, PsycINFO; SAGE, and Scopus. Inaddition, a hand search of Google Scholars was conducted. Inclusion and exclusion criteria were applied to screen the identified data.Findings - From the evidence provided in the eighteen studies identified, the researcher found that current autism research inEAL focused more on teaching strategies and much less on autistic individuals’ EAL learning processes. The 118 autistic participants inthe identified studies displayed highly diverse characteristics, which may explain why the case study was the dominant research approach. They were reported by the identified studies to have strong microlinguistic skills (phonology, morphology, syntax-related) but were weak in macro-linguistic skills (e.g., reading comprehension). The researcher noted that some learning behaviours of autistic students have been reported in addition to some teaching strategies perceived effective for teaching autistic EAL learners such as utilisation of technology and a visual approach.Significance - While there is an increasing number of autistic individuals learning EAL, research on autistic students learning EALand on teaching autistic students EAL has been limited to date. This present study is the first scoping review to investigate existing relevant studies. Despite calling for further investigation into the teaching and learning of autistic students in EAL that involve the perspectives of parents of non-autistic peers, and of the autistic students themselves, interactive patterns of teaching and learning of autistic individuals in EAL classrooms remains an area for further research in the future.